1965
DOI: 10.1177/00220345650440063401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Magnesium Deficiency on the Bones and Teeth of Rats

Abstract: The fact that magnesium is essential for growth has been known for some time. Leroy' was the first to demonstrate that growth was arrested after [9][10][11][12][13][14][15] Irving,6 Becks and Furuta,7 and Yamana and Singer5 have described the changes in the dentin of rats and hamsters. Typical striations occurred in the dentin, which appeared to be imperfectly calcified. The present investigation was undertaken to determine by various histochemical reactions the components of bone and dentin that were affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 17 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…10-16) have been reported [91,[95][96][97][98][99][100][101][102]104,[106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125]. Extrapolating these findings to the domestic cat should be done with caution, however, because the results of these experimental studies are not uniform.…”
Section: Experimental Studies With Vitamin D and Vitamin D Metabolitesmentioning
confidence: 99%
“…10-16) have been reported [91,[95][96][97][98][99][100][101][102]104,[106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125]. Extrapolating these findings to the domestic cat should be done with caution, however, because the results of these experimental studies are not uniform.…”
Section: Experimental Studies With Vitamin D and Vitamin D Metabolitesmentioning
confidence: 99%
“…On the other hand, copper is an essential trace metal existing in living organisms and is necessary for triggering some of the biological processes. Copper is known as an angiogenic reagent due to its role in the increase of proangiogenic expression and stimulation of the human endothelial cell proliferation . Previous reports have suggested that the incorporation of 5 mol% CuO in BG composition can result in a significant antibacterial efficiency, and an improved bone regeneration capability and a higher angiogenesis stimulation compared to copper‐free BGs.…”
Section: Introductionmentioning
confidence: 99%
“…and have been reported sporadically since that time [3][4][5][6]. With few exceptions, microscopic examinations of magnesium-deficient bone have focused on the epiphyseal growth plate [4,7,8]. The width of the epiphyseal growth plate has been found significantly decreased, and in one instance [3], 35SO4 and 3H-methionine uptake at the plate were reported reduced in long bones of magnesium-depleted rats.…”
Section: Introductionmentioning
confidence: 99%